The Effect of Dance Learning and Mother's Attachment on Early Childhood Regulation - Luki Mei Aprida, Astita; Yetti, Elindra; Sarifah, Iva (Murhum : Jurnal Pendidikan Anak Usia Dini, 2024)
This research departs from the fundamental issue of low self-regulation ability in early childhood, a condition that can have negative implications for long-term academic development. In this context, the study aims to explore the extent to which the implementation of dance learning strategies can increase emotional attachment between mothers and children, as well as strengthen self-regulation skills in early childhood. This study adopts a treatment by level 2 x 2 experimental design, which allows in-depth testing of the interaction of independent variables and their impact on dependent variables. The data obtained through observation are focused on two main aspects: the level of mother-child attachment and the child's self-regulation ability. The data analysis technique used is a two-track ANAVA test, which is processed with MS Office Excel 2011 software. The study involved a sample of 28 children aged 5 to 6 years, who were randomly grouped into two groups—14 children in the experimental group and 14 children in the control group—thus allowing for a significant comparison of results between the two groups.